Epilithic Diatoms Diversity in The Reservoir of Universitas Diponegoro, Semarang - Jihan Afifah; Riche Hariyati; Tri Retnaningsih Soeprobowati (Indonesian Society of Limnology, 2021)
Diatom biodiversity is an increasing concern due to growing human impact, the study was carried out in one of the most important water storage reservoirs of Tembalang Region. The anthropogenic activity influence of diatom diversity in the UNDIP Reservoir. The reservoir of Universitas Diponegoro (UNDIP) Semarang was an area of 1.24 km2, with the deepest part of 15 meters, and able to accommodate water up to 13500 m3. This study aims to determine the relative abundance, diversity, evenness, dominance of diatoms and is expected to provide information about the condition of the waters in the Diponegoro University Reservoir, Semarang. Littoral benthic diatoms of five locations were sampled. Diatoms slides were prepared from scraping the rock surface with an area of 3x3 cm, dilute in 50 ml distilled water, and identification under the microscope with 1000 magnification. Analysis of the physical characteristics of the waters includes Temperature, pH, DO, TDS, Conductivity, and Turbidity. The diatom composition in UNDIP Reservoir consists of 72 species that belong to 20 genera. The Shannon-Wiener diversity index (H') ranges from 2-3. The dominance index (D) ranges from 0.05-0.17. The Evenness index (E) ranges from 0.54-0.90. Water quality parameters showed a fairly good value in the growth of diatoms. Dominated by periphytic taxa such as Cyclotella meneghiniana (15.72%), Brachysira microcephala (9.93%), and Achnanthidium minutissima (6.84%) which are widely distributed and live at temperatures of 20-30?C and pH >6.